Improving Cyclic Stability of LiMn2O4/Graphite Battery Under Elevated Temperature by Using 1, 3-Propane Sultone as Electrolyte Additive - Li, Xinxi; Liu, Long; Li, Shumin; Guo, Lin; Li, Bin; Zhang, Guoqing (Frontiers in Materials, 2020)
Spinel lithium manganese oxide (LiMn2O4) based Li-ion battery (LIB) is attractive for hybrid/full electric vehicles because of its abundant resources and easy preparation. However, operation under an elevated temperature could cause severe capacity fading of the spinel cathodes. In this work, 1, 3-propane sultone (PS) is investigated as an electrolyte additive for improving the cyclability of the LiMn2O4/graphite LIB at elevated temperature. The charge and discharge measurement proves that PS can significantly enhance the cyclability of 053048-type LiMn2O4/graphite pouch cell at 60 ◦C. Compared to the cell without additive, the capacity retention of the cell using electrolyte with 5 % PS increases from 52 to 71% after 180 cycles. The improved cyclability is attributable to the modification of the solid electrolyte interface (SEI) on both positive and negative sides of the LiMn2O4/graphite cell by PS, which effectively prevents anode and cathode from structural breakdown and inhibits the electrolyte decomposition.